2016
DOI: 10.5430/jnep.v6n4p136
|View full text |Cite
|
Sign up to set email alerts
|

How midwifery students experience learning conditions in labor wards

Abstract: Midwives are responsible for the well-being of women and babies during labor and birth. Learning midwifery is complex and challenging, and how students are welcomed into the labor wards affects learning. This study aimed to identify and explain the conditions that affected midwifery students' learning in labor wards and their consequences. We used classical grounded theory to analyze longitudinal data from 15 individual and three focus group interviews of 10 postgraduate midwifery students in Norway. The key c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…29 Bunlara ek olarak Brunstad ve ark., 2016 yılında yaptıkları çalışmada, ebelik öğrencilerinin duygularının, öğrenme becerilerini etkilediğini göstermişlerdir. 30 Bu nedenle öğrencilere, deneyimlerini ve duygularını işlemek için yansıtma tekniği gibi farklı öğrenme araçlarının sunulmasının büyük önem taşıdığını söylemek mümkündür.…”
Section: Discussionunclassified
“…29 Bunlara ek olarak Brunstad ve ark., 2016 yılında yaptıkları çalışmada, ebelik öğrencilerinin duygularının, öğrenme becerilerini etkilediğini göstermişlerdir. 30 Bu nedenle öğrencilere, deneyimlerini ve duygularını işlemek için yansıtma tekniği gibi farklı öğrenme araçlarının sunulmasının büyük önem taşıdığını söylemek mümkündür.…”
Section: Discussionunclassified
“…So, it is recommended that student defense should be controlled, and a trustful clinical setting and acceptation of the students should be supplied by the educators and healthcare professionals (15). However, in another study, it was stated that it is not enough by itself to set environmental conditions, but also the senses and the self-concepts of midwifery students should be improved, and this is highly important (16).…”
Section: Discussionmentioning
confidence: 99%
“…Views from other health workers are very critical in facilitating timely referrals complicated cases and these may be attained if there is good collaboration between the midwife and work colleagues [1]. The stress and poor relationships may also affect midwifery students during their clinical experience in labour wards [18]. The authors discovered that student midwives are afraid of being reprimanded for any mistake done in relation to client care.…”
Section: Communication Collaboration Emotions and Perceptionsmentioning
confidence: 99%
“…Mentors ISSN: 2456-7132 Available online at Journals.aijr.in Factors Influencing Midwifery Clinical Decision-making are helpful because they select cases that are relevant for the students' learning. Through the mentors' guidance and counselling, students are able to master the skills [18]. The authors reported that students appreciated mentors who took their time to give feedback on their performance.…”
Section: Mentorshipmentioning
confidence: 99%